Interplay of Linker Functionalization and Hydrogen Adsorption in the Metal–Organic Framework MIL-101 - Szilagyi, Petra; Weinrauch, I.; Oh, H.; Hirscher, M.; Juan-Alcaniz, J.; Serra-Crespo, P.; Trzesniewski, B.; Geerlings, H.; Gascon, J.; Grzech, A.; van de Krol, R.; Geerlings, H. (American Chemical Society, 2014)
Functionalization of metal–organic frameworks results in higher hydrogen uptakes owing to stronger hydrogen–host interactions. However, it has not been studied whether a given functional group acts on existing adsorption sites (linker or metal) or introduces new ones. In this work, the effect of two types of functional groups on MIL-101 (Cr) is analyzed. Thermal-desorption spectroscopy reveals that the -Br ligand increases the secondary building unit’s hydrogen affinity, while the -NH2 functional group introduces new hydrogen adsorption sites. In addition, a subsequent introduction of -Br and -NH2 ligands on the linker results in the highest hydrogen-store interaction energy on the cationic nodes. The latter is attributed to a push-and-pull effect of the linkers.